Attributions of Generation Z University Students Regarding Poverty: The Case of The Department of Labor Economics And Industrial Relations (Third Sector Social Economic Review, 2025)
Poverty is a multidimensional social issue that has affected humanity throughout history and remains a critical concern today. Understanding the causes of poverty and developing appropriate strategies are top priorities for developed and developing countries. In this context, analyzing how Generation Z—soon to take active roles in the labor market and society—perceives the causes of poverty offers a fresh and timely perspective. However, literature addressing Generation Z's perceptions of poverty is notably limited.This study examines the causal attributions of Generation Z undergraduate students regarding poverty and explores the relationship between these attributions and various demographic characteristics. Using a relational screening model, data were collected from 187 students via the Causal Attributions of Poverty Scale (CAPS) and a demographic questionnaire. Findings reveal that students predominantly attribute poverty to structural causes (mean = 4.46), while individual and fatalistic/familial explanations receive lower importance. Statistically significant differences were found between structural attributions and gender as well as household size: female students and those from smaller households emphasized structural factors more than their counterparts. On the other hand, no significant associations were found between causal attributions and variables such as class level, academic achievement, or household income.These findings underline the importance of focusing on structural inequalities when developing poverty-related social policies, especially through the lens of younger generations.
Keywords: Poverty; Generation Z; Causes of Poverty; Structural Poverty; University Students